China's international terrorist problem - Pantucci, Raffaello (2023)
The pattern of terrorist attacks in Pakistan shows that it is those motivated by separatist or other political motivations – and not jihadist ones – that are currently the ones that pose the most serious threats to Chinese interests around the world.